Talar OsteoPeriostic Grafting from the Iliac Crest (TOPIC): Five-Year Prospective Results of a Novel Press-Fit Surgical Technique for Large, Complex Osteochondral Lesions of the Talus - Julian Hollander Bsc; Jari Dahmen MD; Sjoerd Stufkens MD, PhD; Gino M M.M.J. Kerkhoffs MD, PhD (Foot & Ankle Orthopaedics)
Category: Ankle; Ankle Arthritis Introduction/Purpose: Osteochondral lesions of the talus (OLT) are lesions that affect both the articular cartilage and underlying subchondral bone that often arise after trauma. Large OLTs may be treated using osteochondral autografts, for example from the ipsilateral knee. This, however, often results in donor site morbidity. Moreover, the cylindric nature of the osteochondral grafts does not allow for a perfect fit for the defect. The novel technique Talar OsteoPeriostic grafting from the Iliac Crest (TOPIC) overcomes these challenges by using an osteoperiosteal autograft of the ipsilateral iliac crest. The aim of the present study is to prospectively evaluate the clinical, radiological and safety outcomes after 5 years of follow-up for patients who underwent the new TOPIC procedure for an OLT. Methods: A prospective cohort study of patients who underwent the TOPIC procedure was conducted. The primary outcome was the Numeric Rating Scale (NRS) of pain during walking. Other clinical outcomes included the NRS during rest and stair climbing, the Foot and Ankle Outcome Score (FAOS) and the Mental Component Score (MCS) and Physical Component Score (PCS) of the Short Form-36 (SF-36). In addition, the AOFAS ankle-hindfoot score was measured. All clinical outcomes were measured preoperatively and after 6 months, 1 year, 2 years and 5 years of follow-up. Computed tomography (CT) scans were performed preoperatively and postoperatively at 12 weeks, 1 year, 2 years and 5 years to assess osteotomy union, graft consolidation and graft cyst development. In addition, complications and hardware removal were evaluated. Results: 36 patients (current data is 29pt; expected to be complete at congress) were assessed, and no patient were lost to follow-up. The NRS of pain during walking improved from 6.5 [5-8] preoperatively to 2 [1-3] at 5-year follow-up (p < 0.001). The NRS during rest and stair climbing improved with 2 (p = 0.002) and 4 points (p < 0.001), respectively. All FAOS subscales improved significantly. The SF-36 PCS improved (32 to 35; p = 0.059) and the MCS improved (39 to 47; p < 0.001). The AOFAS improved from 52 to 90 (p < 0.001). There was 100% union at the osteotomy site after 12 weeks and 100% of the graft showed consolidation at 1, 2 and 5 years postoperatively. No major complications occurred. Conclusion: The TOPIC procedure is an effective treatment option for large osteochondral lesions of the talus, with durable results after 5 years of follow-up. A significant improvement in clinical outcomes was observed, with excellent radiological results. No major complications were recorded.